Review and Analysis of Peak Tracking Techniques for Fiber Bragg Grating Sensors - Tosi, Daniele (Sensors, 2017)
Fiber Bragg Grating (FBG) sensors are among the most popular elements for fiber optic sensor networks used for the direct measurement of temperature and strain. Modern FBG interrogation setups measure the FBG spectrum in real-time, and determine the shift of the Bragg wavelength of the FBG in order to estimate the physical parameters. The problem of determining the peak wavelength of the FBG from a spectral measurement limited in resolution and noise, is referred as the peak-tracking problem. In this work, the several peak-tracking approaches are reviewed and classified, outlining their algorithmic implementations: the methods based on direct estimation, interpolation, correlation, resampling, transforms, and optimization are discussed in all their proposed implementations. Then, a simulation based on coupled-mode theory compares the performance of the main peak-tracking methods, in terms of accuracy and signal to noise ratio resilience.
Keywords: Fiber Bragg Grating (FBG); optical fiber sensors; optical sensors; peak tracking; wavelength shift estimation; Research Subject Categories::NATURAL SCIENCES::Physics::Other physics::Optics